S-genotyping of 25 sweet cherry (Prunus avium L.) cultivars from the Czech Republic. Issue 2 (3rd March 2016) - Sharma, K.; Cachi, A. M.; Sedlák, P.; Skřivanová, A.; Wünsch, A.
ABSTRACT: Sweet cherry ( Prunus avium L.) is a self-incompatible species. Determination of the S -genotypes of cherry cultivars is crucial for breeding and to select appropriate cultivars for cross-fertilisation and fruit set. In this study, we characterised the S -genotypes of 25 sweet cherry cultivars, some of which had being bred at the Research and Breeding Institute of Pomology (RBIP), Holovousy, Czech Republic, and others were European cultivars in the RBIP collection. S -genotyping was carried out by polymerase chain reaction using consensus primers for the S-RNase and SFB genes, and capillary electrophoresis. Nine different known S- haplotypes ( S1, S2, S3, S4, S5, S6, S9, S13, and S16 ) were identified and the cultivars were assigned to 12 incompatibility groups. One local cultivar, 'Ptačka z Plzně', originated from a wild forest seedling and used as a pollinator, was assigned to Group 0 of universal donors. The pedigree of some cultivars was confirmed by their S -genotype. This study represents the ﬁrst comprehensive S -genotype screening of sweet cherry genetic resources in the Czech Republic and will be useful for the design of crossing programmes and orchard management of these sweet cherry cultivars.